Wanderers Literature, Culture and the Open Road - Brown Morris, David (Routledge Focus on Literature, 2022)
This book introduces the idea and experience of wandering, as reflected in cultural texts from popular songs to philosophical analysis, providing both a fascinating informal history and a necessary vantage point for understanding - in our era - the emergence of new wanderers. 　 Wanderers offers a fast-paced, wide-ranging, and compelling introduction to this significant and recurrent theme in literary history. David Brown Morris argues that wandering, as a primal and recurrent human experience, is basic to the understanding of certain literary texts. In turn, certain prominent literary and cultural texts (from Paradise Lost to pop songs, from Wordsworth to the blues, from the Wandering Jew to the film Nomadland) demonstrate how representations of wandering have changed across cultures, times, and genres. Wanderers provides an initial overview necessary to grasp the importance of wandering both as a perennial human experience and as a changing historical event, including contemporary forms such as homelessness and climate migration that make urgent claims upon us. 　 Wanderers takes you on a thoroughly enjoyable and informative stroll through a significant concept that will be of interest to those studying or researching literature, cultural studies, and philosophy.